NOTION OF JUDICIAL ETHICS – A COMPARATIVE STUDY - KUMAR , P. VASANTHA (International Journal of Psychosocial Rehabilitation, 2020)
Judiciary nevertheless retained its image as one of the few institutions of the country, which is still above the deterioration, that prevails in most organs of the State.